A personalization application development for online shopping / Army Karmila Zakaria - Army Karmila, Zakaria (2006)
Nowadays, the emergence of personalization application for online shopping in business industries is new approach to help business owners gain most benefits for their companies. E-Commerce, with the Internet as its main platform has a very large market network. Because of these, a personalization application development for online shopping system will be developed for Syarikat Perabot Jati Selayang. The development of the system is to help customer to find their product based on their preference. The system provides facilities for customers to place order, purchase and a recommend product based on customer needs electronically. The system developed in the Windows environment using PHP as the scripting language. While, MySQL is used as the database management system. During the development process, the System Development Life Cycle (SDLC) is implemented where it acts as a methodology in developing the system. The development of such system is expected to be the driver for the growth of product sales and market